2011
DOI: 10.1074/jbc.m110.197152
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Domains of Melanosome Matrix Protein Pmel17 Orthologs Form Amyloid Fibrils at the Acidic Melanosomal pH

Abstract: Most amyloids are pathological, but fragments of Pmel17 form a functional amyloid in vertebrate melanosomes essential for melanin synthesis and deposition. We previously reported that only at the mildly acidic pH (4 -5.5) typical of melanosomes, the repeat domain (RPT) of human Pmel17 can form amyloid in vitro. Combined with the known presence of RPT in the melanosome filaments and the requirement of this domain for filament formation, we proposed that RPT may be the core of the amyloid formed in vivo. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 54 publications
3
57
0
Order By: Relevance
“…Briefly, the melanin precursor (MP) is activated by a tyrosinase (T) resulting in the activated melanin precursor (AMP), which interacts with the amyloidogenic sequence PmeI17 (PmeI) leading to mature melanin. [91][92][93] assembled to microtubes, has been explored for effectively deliver drugs. Using rhodamine as a model drug, it was shown that the FF microtubes released the drug in a steady-state profile, following first-order kinetics.…”
Section: Amyloid-based Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the melanin precursor (MP) is activated by a tyrosinase (T) resulting in the activated melanin precursor (AMP), which interacts with the amyloidogenic sequence PmeI17 (PmeI) leading to mature melanin. [91][92][93] assembled to microtubes, has been explored for effectively deliver drugs. Using rhodamine as a model drug, it was shown that the FF microtubes released the drug in a steady-state profile, following first-order kinetics.…”
Section: Amyloid-based Drug Deliverymentioning
confidence: 99%
“…Here, the Pmel17 amyloid fibers, found in melanosomes, serve as a template for the polymerization of the pigment melanin. 92 Hence, Pmel17 strikes a remarkable balance, being a non-pathological functional amyloid in humans. Also, the peptide hormones corticotropin-releasing hormone (CRH), human prolactin (hPRL), and somatostatin, the growth hormone inhibitor hormone (GHIH), are other examples that transform at high concentrations into amyloid fibrils.…”
Section: Balancing Fibril Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no evidence of amyloid accumulation either in skin samples or in skin keratinocytes when co-cultured with normal human melanocytes (JVC, unpublished data). One possible reason for this is that PMEL amyloid formation is sensitive to pH [7]. Thus, the neutral pH in the extracellular compartment most likely undermines PMEL amyloid fiber ability or if any amyloid is formed it is dissolved; while the intra organelle acidic pH (5.0) will favor amyloid formation.…”
Section: A N-glycosylation In Pmelmentioning
confidence: 99%
“…Early reports suggested that two domains inside PMEL are contributors to fibril formation [5]. Today, unequivocal evidence recognizes that the so called repeat (RPT) domain is the only region capable to form amyloid fibrils in vivo and in vitro [6][7][8]. Unlike disease-associated amyloids, functional amyloids are the product of coordinated and regular cellular processes that ensure that amyloidogenesis does not result in cell damage or death [2;9].…”
Section: Introductionmentioning
confidence: 99%